У=2х + 1; у=0; х=1; х=2. у= х + 5; у=0; х=1; х=3.
у= 3х - 2; у=0; х=1; х= 2
у= х – 3; у=0; х=5; х= 2
у=2х – 2; у=0; х=2; х= 4
у= 4х + 1; у=0; х=1; х= 2
у= 3 – х; у=0; х= -1; х= 2
у= 3х + 1; у=0; х=1; х= 2
у= х – 1; у=0; х=3; х= 5
у= 5х – 2; у=0; х=1; х= 2
у= 2х + 3; у=0; х= -1; х= 2
у= 2х + 4; у=0; х= -1; х= 2
у= 1 – х; у=0; х= -3; х= -1
у= 2х – 2; у=0; х=2; х= 4
у= 5х – 1; у=0; х=1; х= 2
у= х + 3; у=0; х= -2; х= 2
у= 4х – 2; у=0; х=1; х= 3
у= 3х + 2; у=0; х=1; х= 2
у= 2 – 3х; у=0; х= -2; х= 0
у= х + 4; у=0; х= -2; х= 2

bebe13 bebe13    2   20.12.2020 15:33    3

Другие вопросы по теме Математика